Manajemen Pengorganisasian Program Kursus Bahasa Arab di Akademik Almadinah - Ghufran Akbar; Bambang Budi Prasetyo (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah, 2022)
Organizing is the second step in organizational management while the first step is. careful planning will not work perfectly, if no one runs and also moves, without clarifying the work and who will do it. Talking about the right organization, we are talking about organizing that can produce starting from its form, work system, structure, resources, and also other aspects. In this study, what will be discussed are: Organizational management in Almadinah Academy's online Arabic program, Division of tasks in organizing Almadinah Academy's online Arabic program. This study uses a descriptive qualitative research method. Data was collected by using interview techniques and direct observation to one of the teachers who teach at the institution. After the data is collected, data analysis is carried out by: data reduction, data presentation, conclusion drawing/verification. From this research, it can be seen that the organizational management of the Almadinah Academy online language program uses a coordination system that can be seen from the manager's duties under the auspices of the general chairman, after coordinating with staff (coords per department), and in each program in the language department. This is because Arabic programs and organizations in general have a line and staff organization model.